Szlachecka corka - Borovsky, Natasha; Borovsky, Natasha (Warszawa : Wydawn. Alfa, 1993)
The story of an aristocratic young girl who wants to preserve the old way in the midst of the social upheaval of the Russian empire from 1890 to 1920.
Translation of: A daughter of the nobility.
Keywords: World War, 1914-1918 -- Fiction; Russia -- History -- Nicholas II, 1894-1917 -- Fiction; Soviet Union -- History -- Revolution, 1917-1921 -- Fiction